Les propietats d'«agradar»: estructura temàtica i comportament sintàctic - Gemma Rigau (Caplletra: Revista Internacional de Filologia, 2015)
In this article, we show that Belletti-Rizzi's (1987) analysis of Italian psychological verbs is not available for Catalan psychological verbs. We analyze the thematic grid and the syntactic properties of this verbal class. There is enough evidence that the subject of agradar 'to please' does not behave like a derived subject, like the subject of an unaccusative verb.